Mutation Study of 28 Autosomal STR Loci in Southwest Chinese Han Population. (December 2015) - Zhu, W.Q.; Jin, B.; Su, Q.; Luo, H.B.; Li, Y.B.; Wu, J.; Yan, J.; Hou, Y.P.; Liang, W.B.; Zhang, L.
Abstract: In this study, mutation rates and 95% CI of 28 autosomal STR loci were investigated based upon appropriately 100, 000 parent(s)-child meiotic transfers obtained from 5569 paternity testing cases in southwest China. Overall, 169 mutation events were observed. 168 events (99.4%) were single-step mutations, only 1 event (0.59%) was double-step mutation. The average mutation rate was 17.01 × 10 −4 . The locus-specific mutation rate varied from 4.39 × 10 −4 to 59.12 × 10 −4 . There was no significant difference between mutation expansion and contraction (∼1.09:1). Paternal origin mutations occurred more frequently than maternal origin ones (∼3.45:1).